Using a Kinase‐Inducible Bimolecular Switch to Control Enzyme Activity in Living Cells. Issue 3 (1st October 2013) - Mehta, Sohum; Zhang, Jin
Abstract: Molecular switches have been instrumental in the development of powerful and versatile genetic tools for directly probing biochemical processes, such as intracellular signaling, within their native contexts. A molecular switch can be broadly defined as a molecular system capable of existing in either of two states (e.g., conformations), which can be converted from one state to the other by a specific input stimulus. This protocol outlines a method for using a kinase‐inducible bimolecular switch, along with live‐cell fluorescence microscopy, to directly control and monitor the activity of a specific enzyme in living cells. Curr. Protoc. Chem. Biol . 5:227‐237 © 2013 by John Wiley & Sons, Inc.